Resonant switched capacitor voltage multiplier with interleaving capability - J.E. Valdez-Reséndiz; A. Claudio-Sánchez; Rosas-caro, Julio; G.V. Guerrero-Ramírez; A. Tapia-Hernández (My University, 2016)
This paper presents a switched capacitor voltage multiplier with resonant-type current between capacitors; these current waveforms are achieved by designing a resonant topology combined with a safe switching strategy. Moreover, the proposed converter provides interleaving capability, soft switching, modular structure and a reduced number of components. These features yield a low cost converter with high voltage gain scalability, reduced input current ripple and limited peak currents between capacitors. Experimental results that corroborate the advantages of the proposed topology are presented.